Diagnosis of arithmetic-algebraic lag in rural high school students: Impact of the COVID-19 pandemic on fundamental mathematical competencies at CETIS 167, Milpa Alta - López, Pavel David Ulises Avendaño; Torres, Arturo González; Bojorges, Gerardo Quiroz; Echeagaray, Melissa Edith Salazar (Edelweiss Applied Science and Technology, 2025)
The purpose of this study was to identify the academic and socioeconomic conditions that influence the learning of algebra and arithmetic in students at CETIS No. 167, in the municipality of Milpa Alta, considering the effects of the COVID-19 pandemic. The research was guided by a quantitative paradigm, with a non-experimental, correlational approach, whose methodology considered the application of two instruments: a diagnostic evaluation of 16 items and a survey of parents, with 21 items, for a sample of 301 students with scientific intent. Based on the above, it was determined that 65.44% of the students have problems with the hierarchy of operations and algebraic reasoning, which can be due to the fact of having no classes in person and the insufficient use of papers. It was also observed that 40.2% do not have family members professionally trained, affecting the generalization of the students' academic achievement expectations. The conclusion was drawn that the development of practical teaching strategies mediated by technology is needed in order to develop mathematics skills and context-based learning.